2012
DOI: 10.1002/ccd.23507
|View full text |Cite
|
Sign up to set email alerts
|

Embolic protection device utilization during stenting of native coronary artery lesions with large lipid core plaques as detected by near‐infrared spectroscopy

Abstract: Use of EPDs frequently resulted in embolized material retrieval after stenting of native coronary artery lesions with large LCPs. These findings support further study of EPDs as a means to prevent poststenting MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Brilakis et al (19) reported that use of a filter-based catheter in the native coronary circulation before PCI of high-risk plaques may protect the distal microvasculature from embolization. Whether native coronary artery lesions prone to periprocedural myonecrosis can be identified before PCI and whether the use of a distal embolic protection device can reduce the incidence of periprocedural MI in high-risk lesions so identified have never been prospectively examined in a multicenter trial.…”
mentioning
confidence: 98%
“…Brilakis et al (19) reported that use of a filter-based catheter in the native coronary circulation before PCI of high-risk plaques may protect the distal microvasculature from embolization. Whether native coronary artery lesions prone to periprocedural myonecrosis can be identified before PCI and whether the use of a distal embolic protection device can reduce the incidence of periprocedural MI in high-risk lesions so identified have never been prospectively examined in a multicenter trial.…”
mentioning
confidence: 98%
“…Distal embolization, as an important mechanism of periprocedural MI, was further supported by several studies that have demonstrated a significant decrease in the size of LCP after stenting [122][123][124]. Stone et al showed in the CANARY trial that LCP measured as LCBI by NIRS in the stented vessels reduces with PCI treatment, with a significant reduction of median LCBI from 143.2 before PCI to 17.9 after PCI (P < 0.001) [125].…”
Section: Prevention Of Periprocedural Complicationsmentioning
confidence: 91%
“…Second, fibroatheroma detection within a lesion for which PCI is planned suggests a high risk for periprocedural myocardial infarction (9,10) due to distal embolization and/or aggressive in situ thrombus formation (11). Potential clinical strategies to mitigate this risk include vasodilator administration (nicardipine is the authors' preferred medication due to longer half-life and modest hypotensive effect), aggressive anticoagulation (with addition of a glycoprotein IIb/IIIa inhibitor, which is usually given as bolus only without post-PCI infusion), attempts for plaque "vaporization" (e.g., by using laser), and deployment of an embolic protection device (usually a filter that can capture both embolized plaque and/or thrombus) (12).…”
Section: Fibroatheroma Detected: Now What?mentioning
confidence: 99%